The Role of Negative Emotions in Climate Change Awareness Advertising - Sylvia Eirini Chalkiadaki; Sebastian Vaida (Babes-Bolyai University, 2023)
The field of advertising has been increasingly using psychological concepts to push consumers towards buying and changing their attitudes about the product and even about the whole brand. Accordingly, using emotions as a tool for persuasion and raising behavioural intention should be discussed from a psychological point of view. Therefore, this paper aims to provide an extensive explanation and an experimental proposal for the relationship between three distinct negative emotions and behavioural intention in the context of video advertising. The main advertising concept that we have discussed is the awareness of advertising campaigns, specifically ones on the topic of climate change. In addition, to increase the specificity of the information presented, we analysed several emotions individually: fear, guilt and anger, and their potential of inducing behavioural intention. The three negative distinct emotions were chosen specifically because of the motivational factor that they include, if used in certain conditions, they induce a drive for action, a want for behavioural change - which is preferable in awareness campaigns. We have also discussed some technical details that can be considered important when creating emotional appeals - especially anger, fear or guilt inducing. This paper also offers future directions and represents a guideline for creating emotion inducing advertisements. On top of that, it represents proof that the field of advertising can benefit from research in the psychological field, and that publicity can be used not only as a means for persuading consumers, but also shifting behaviours towards sustainability.